The dog as an animal model for bladder and urethral urothelial carcinoma: comparative epidemiology and histology - de Brot, Simone; Robinson, Brian D.; Scase, Tim; Grau‑Roma, Llorenç; Wilkinson, Eleanor; Boorjian, Stephen A.; Gardner, David S.; Mongan, Nigel P. (Spandidos Publications, 2018)
Despite the recent approval of several novel agents for patients with metastatic urothelial carcinoma (UC), survival in this setting remains poor. As such, continued investigation into novel therapeutic options remains warranted. Pre clinical development of novel treatments requires an animal model that accurately simulates the disease in humans. The aim of the present study was to evaluate the dog as an animal model for human UC. A total of 260 cases of spontaneous, untreated canine primary urethral and urinary bladder UC, were epide¬miologically and histologically assessed and classified based on the current 2016 World Health Organization (WHO) tumor classification system. Canine data was compared with human data available from scientific literature. The mean age of dogs diagnosed with UC was 10.22 years (range, 4 15 years), which is equivalent to 60 70 human years. The results revealed a high association between UC diagnosis with the female sex [odds ratio (OR) 3.51; 95% confidence interval (CI) 2.57 4.79; P<0.001], surgical neutering (OR 4.57; 95% CI 1.87 11.12; P<0.001) and breed (OR 15.11 for Scottish terriers; 95% CI 8.99 25.41; P<0.001). Based on the 2016 WHO tumor (T), node and metastasis staging system, the primary tumors were characterized as T1 (38%), T2a (28%), T2b (13%) and T3 (22%). Non papillary, flat subgross tumor growth was strongly associated with muscle invasion (OR 31.00; P<0.001). Irrespective of subgross growth pattern, all assessable tumors were invading beyond the basement membrane compatible with infiltrating UC. Conventional, not further classifiable infiltrating UC was the most common type of tumor (90%), followed by UC with divergent, squamous and/or glandular differentiation (6%). Seven out of the 260 (2.8%) cases were classified as non urothelial based on their histological morphology. These cases included 5 (2%) squamous cell carci¬nomas, 1 (0.4%) adenocarcinoma and 1 (0.4%) neuroendocrine tumor. The 2 most striking common features of canine and human UC included high sex predilection and histological tumor appearance. The results support the suitability of the dog as an animal model for UC and confirm that dogs also spontaneously develop rare UC subtypes and bladder tumors, including plasmacytoid UC and neuroendocrine tumor, which are herein described for the first time in a non experimental animal species.